Impact of K-Pop Idol Dating Scandals on Fans' Parasocial Relationships with Idols: Comparing Indonesian and South Korean Fans - Dewanggi, Ni Made Prami; Septarini, Berlian Gressy (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2025)
The rapid growth of the K-Pop industry has intensified the negative impact of dating scandals on parasocial relationships between fans and idols. This study examines cultural differences in how Indonesian and South Korean K-Pop fans respond to such scandals, which may lead to parasocial breakups. Based on parasocial relationship theory and employing a qualitative comparative design, six participants, three from each country, were recruited through convenience sampling. Findings reveal that fans experienced both positive and negative emotions, including acceptance and endorsement. South Korean fans tended to respond more negatively, whereas Indonesian fans displayed greater positivity and support toward their idols. By highlighting significant cultural differences, these findings provide insights into the dynamics of fan–idol relationships and emphasize the importance of fostering supportive and healthy fan cultures to mitigate the psychological impact of dating scandals on idols.